PENGARUH PRINSIP KERAHASIAAN BANK TERHADAP TINDAK PIDANA PENCUCIAN UANG - fitriah faisal (Al-Amwal : Journal of Islamic Economic Law, 2018)
There are two purpose of this research : (1) To know the relation between bank secrecy principle and the emergence of money laundering cases (2) To know how bank secrecy principle can solve money laundering cases. This research is normative research. The result of this research is bank secrecy principle has a link with money laundering cases, so the banking sector is the safe place to save money from money laundering cases. Bank Secrecy Principle is a barrier in law enforcement, Law enforcer should be admired Bank Secrecy Principle because Bank Secrecy Principle is an essential thing in Banking Sector as a trusted sector.